2012
DOI: 10.1007/s13726-012-0083-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of environment friendly used rubber powder modified pulp sediments composites

Abstract: In recent years, with growing contradiction between energy supply and demand, the more and more high demand of the environmental protection is needed. The work represented an environment friendly method for recycling of waste rubber and pulp sediment that a new composite material was prepared using pulp sediment as the matrix, used rubber powder as the toughening agent, and sawdust as the reinforcement. The effects of used rubber powder content on the mechanical properties of the pulp sediment and sawdust/pulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The curing and cross-linking mechanism of thermosetting epoxy resin is very complex and intricate. The chemical kinetics and physical interactions both exist in the curing process [10][11][12], which has so far not been understood thoroughly. The phenomenological method is the most popular and commonly adopted in studying epoxy resins.…”
Section: Curing Of Epoxy Resinmentioning
confidence: 99%
“…The curing and cross-linking mechanism of thermosetting epoxy resin is very complex and intricate. The chemical kinetics and physical interactions both exist in the curing process [10][11][12], which has so far not been understood thoroughly. The phenomenological method is the most popular and commonly adopted in studying epoxy resins.…”
Section: Curing Of Epoxy Resinmentioning
confidence: 99%
“…They found that, up to 20% of waste rubber loading by volume, given satisfactory properties of concrete. Besides that, Wu and Zhang 14 Wu and Zhang 17 developed new pulp sediment composite by using waste rubber powder and pulp sediment as matrix. They found that, the physical properties of waste rubber-pulp sediment composite were comparable with conventional pulp sediment composite.…”
mentioning
confidence: 99%